Peran Dinas Tenaga Kerja Kota Bontang Dalam Meningkatkan Daya Serap Industri Terhadap Lulusan Sekolah Menengah Atas (Sma) Dan Kejuruan (Smk) - Irianto (BEduManagers Journal : Borneo Educational Management and Research Journal, 2025)
This study analyses the role of the Bontang City Manpower Office (Disnaker) as a facilitator and coordinator in increasing the absorption capacity of local industries for senior high school/vocational school graduates. The main issues are the skills gap and high open unemployment rate among young graduates, especially in cities with large industrial sectors such as Bontang. The method used is descriptive qualitative, with data obtained through in-depth interviews with Disnaker, industry representatives (including large companies), and school management, as well as analysis of documents related to training and manpower placement work programmes. The main focus was on the implementation of the Special Job Exchange (BKK), Competency-Based Training (PBK), and apprenticeship programmes facilitated by the Manpower Office. The results of the study show that the Bontang City Manpower Office has played an active role in three main functions: (1) Regulator, through the issuance of local regulations on training; (2) Facilitator, by providing Job Fair and PBK facilities that are aligned with industry needs; and (3) Coordinator, bringing together industry, educational institutions and job seekers.